Impact of neoadjuvant chemotherapy on tumour volume in unilateral Wilms tumour histotypes: a retrospective study - Sara Benlhachemi; Mohammed Khattab; Kenza Hattoufi; Redouane Abouqal; Elmostafa El fahime (BMC Cancer)
Abstract Background Wilms tumour (WT), the most common paediatric kidney tumour, is treated in Morocco following the SIOP protocol, which practices neoadjuvant chemotherapy (NAC). The response to NAC can be assessed by considering both tumor volume reduction and the proportion of therapy-induced changes observed in histological specimens, including necrosis. This retrospective study assesses the impact of NAC on tumour volume across various WT histotypes and correlates these changes with proportions of therapy-induced necrosis. Methods We analysed imaging data and anatomopathological reports, before and after NAC, of 56 patients with unilateral WT, admitted to the children’s hospital in Rabat, from January 2014 to February 2018. Results NAC significantly reduced tumour volume in 82% of WT cases, with an average decrease of 65% in tumour size, with a p < 0.001. Notably, the regressive, blastemal, and mixed types exhibited the most significant response to NAC, in 94%, 82%, and 92% of cases, with p < 0.001, 0.010, 0.002, respectively. The epithelial type showed a decrease in tumour volume in 73% of cases, with p = 0.041. Whereas, the stromal type did not exhibit a significant decrease in tumour volume following NAC (p = 0.790). Moreover, tumor volume decreased by 43% in one case with focal anaplasia and blastemal type, but increased by 7% in the other case with focal anaplasia and regressive type. The change in tumour volume and necrosis demonstrates a moderate negative correlation (Rho = -0.428; p < 0.001). An increase in the proportion of necrosis is associated with a decrease in tumor volume. Conclusion Our findings show a significant reduction in tumour size following NAC in all WT histotypes, with the exception of the stromal type, suggesting the need for alternative strategies, such as intensified treatment or initial nephrectomy for operable tumours.